Uma proposta de interface cérebro-computador para comando de cadeiras de rodas - Ferreira, André (2008)
The implementation of a Brain-Computer Interface (BCI) based on visual stimuli (ERD/ ERS) to command a robotic wheelchair and to stablish a communication interface is presented in this Thesis. The BCI has been developed for impaired people who keep the ability to close/open the eyes, in order to generate the brain patterns here discussed. Experiments carried out with such users, including some with severe neuromuscular disorders, have shown quite promising results. For the users without the capacity of closing/opening the eyes, some changes in the BCI are also proposed. The paradigm used in the BCI is changed from visual stimuli to hands motor imagery. Using such paradigm, the user is supposed to imagine some movements of his/her hands in order to send commands to the robotic wheelchair or the communication interface. Experiments involving both visual and motor imagery paradigms with four severely impaired people and four voluntaries without neuromuscular disorders are here reported. The results are discussed in details and show the feasibility of the proposed BCI.